2006
DOI: 10.1063/1.2163268
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural changes of silver nanoparticles during photochromic transformation

Abstract: Silver nanoparticles embedded in titanium oxide change their color upon irradiation with visible light. Here we investigate the origin of this photochromic effect. The color change is found to result chiefly from a reduction of the optical extinction peak of the photoexcited particle plasmons. From a comparison with x-ray diffraction experiments, we conclude that this reduction is caused by a photoinduced decrease of the mean size of the silver nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 17 publications
1
50
0
1
Order By: Relevance
“…Although the synthesis of Ag/TiO 2 heterostructures was intensively reported in large quantities [8][9][10][11][12][13][14]23,24], there are few reports about Ag/TiO 2 composite thin films with amounts of Ag > 18 mol%, prepared by chemical methods such as sol-gel, so far in the literatures. It is well reported that incorporating larger amount of Ag particles was limited by the sol-gel dip-coating method of up to 18 mol% due to Ag particles coalescing with each other into huge particles during sintering [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the synthesis of Ag/TiO 2 heterostructures was intensively reported in large quantities [8][9][10][11][12][13][14]23,24], there are few reports about Ag/TiO 2 composite thin films with amounts of Ag > 18 mol%, prepared by chemical methods such as sol-gel, so far in the literatures. It is well reported that incorporating larger amount of Ag particles was limited by the sol-gel dip-coating method of up to 18 mol% due to Ag particles coalescing with each other into huge particles during sintering [25].…”
Section: Introductionmentioning
confidence: 99%
“…The early methods [17][18][19], to produce noble-metal nanoparticles are still used today and continue to be the standard by which other synthesis methods are compared [20][21][22]. In particular, silver as a noble metal has attracted considerable attention, as a result of its remarkable role in the improvement of the photo-activity of semiconductors [9,13,23]. They could be reused, and handled more easily and economically if impregnated on substrates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…L'argent s'avĂšre quant Ă  lui ĂȘtre le mĂ©tal noble le plus favorable Ă  l'obtention de couleurs variĂ©es. DiffĂ©rents travaux rapportent un comportement photochromique avec des particules d'argent rĂ©duites au sein de matrices poreuses de TiO 2 de maniĂšre photocatalytique [5,[7][8][9][10], chimique [11,12] ou thermique [12,13] tout autant qu'avec des particules d'argent dĂ©posĂ©es par pulvĂ©risation magnĂ©tron [14,15] ou par voie Ă©lectrochimique [10]. On trouve des matrices poreuses prĂ©parĂ©es Ă  partir de NPs de TiO 2 commerciales cristallisĂ©es dans la phase anatase [5,7,8,10] ou bien Ă©laborĂ©es par voie sol-gel sous forme de films mĂ©soporeux de TiO 2 amorphe [9,[11][12][13].…”
Section: Introductionunclassified